PENGGUNAAN KANTONG KAIN (TOTE BAGS) PENGGANTI KANTONG PLASTIK PADA REMAJA KOTA DENPASAR - NI LUH WIDYASARI; NI MADE WEDAYANI; NI NYOMAN TRI GITAYANI (Universitas Mahasaraswati K. Mataram, 2024)
The phenomenon of reducing the use of plastic bags is an important concern that still continues to be socialized nowadays since it is related to the issue of sustainable environmental pollution. In relation to that phenomenon, this study focused on the existence of tote bags as the substitute of plastic bags that are used by people while doing shopping. It aims to analyze the enthusiasm of teenagers in using the tote bag as the action to decrease the plastic usage in the environment. The data of this study were collected by fulfilling the questionnaire which involved 100 teenagers in the Denpasar City as respondents. The findings of this study indicate that the awareness, understanding, and influence of the social environment are important factors for Denpasar City teenagers in implementing plastic bag diet behavior. As many as 36% of teenagers in Denpasar City rarely receive plastic bags when shopping, and 53% of the respondents always provide tote bags as a substitute for plastic bags when do shopping. Based on the result of the likert scale, the data shows the effectiveness of the regulation in reducing the use of plastic bags in Denpasar City can be categorized as the effective ones